2020
DOI: 10.1159/000508416
|View full text |Cite
|
Sign up to set email alerts
|

Development of Predictive Risk Models of Postpartum Stress Urinary Incontinence for Primiparous and Multiparous Women

Abstract: Objectives: To develop risk predictive models of postpartum stress urinary incontinence (SUI) for both primiparous and multiparous women. Materials and Methods: From July 2016 to July 2017, 815 singleton pregnant women without incontinence before pregnancy who were 18 years or older and admitted to 2 hospitals in Shenzhen, China, were enrolled. Pregnancy-related data were collected at enrollment. Delivery information was obtained from electronic medical records. Telephone follow-up was conducted to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…[ 12 ] Previous studies [ 13 , 14 ] have reported that pregnant women with urine leakage symptoms during pregnancy are more than twice as likely to have urine leakage again within 15 years after delivery than pregnant women without urine leakage symptoms during pregnancy. Studies [ 15 – 17 ] have pointed out that urinary incontinence during pregnancy can double the risk of postpartum urinary incontinence, and primiparas without urinary incontinence before pregnancy are considered the best clinical model for normal pelvic tissue function. Therefore, we took primiparas as the research population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Previous studies [ 13 , 14 ] have reported that pregnant women with urine leakage symptoms during pregnancy are more than twice as likely to have urine leakage again within 15 years after delivery than pregnant women without urine leakage symptoms during pregnancy. Studies [ 15 – 17 ] have pointed out that urinary incontinence during pregnancy can double the risk of postpartum urinary incontinence, and primiparas without urinary incontinence before pregnancy are considered the best clinical model for normal pelvic tissue function. Therefore, we took primiparas as the research population.…”
Section: Discussionmentioning
confidence: 99%
“…As a practical and visual prediction tool, a nomogram can provide valuable information for clinical decision-making. In the field of obstetrics, Chen et al established a prediction model for postpartum SUI in primiparas and multiparas based on clinical factors, and the C-indexes of the model were 0.763 and 0.783 respectively [ 8 ]. Grobman et al established a model to predict the success rate of vaginal delivery after cesarean section to provide information for decision-making by obstetricians [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSUI is a major public health problem that significantly affects postpartum women both in physical and mental health. [8][9][10][11][12]25] Although surgery, medications and PFMT can reach a certain curative effect, there are shortcomings like difficult training techniques, adverse reaction of drugs and surgery. [3,[13][14][15][16] Acupuncture is a treatment method with fast curative effect and small side effect, which can improve PSUI symptoms by promoting nerve reinnervation, enhancing pelvic floor muscle strength and improving muscle coordination.…”
Section: Discussionmentioning
confidence: 99%